The possibility of increasing the quantity of oxygenate s in fuel blends with no diesel engine modifications - Raslavičius, Laurencas; Bazaras, Žilvinas (Transport, 2010)
Two fuel kinds of organic origin including rapeseed methyl ester (RME) and ethanol (E) were selected for their different physical-chemical parameters to study the maximum apt volume of oxygenates to mix fossil diesel (D) and establish expectancy to apply D–RME–E blend as a fuel for the unmodified high–speed diesel engine (a combustion chamber consists of a dished piston). The objective of the article is to provide an explicit relationship between the nature of fuel composition and diesel engine operating parameters. The results of the carried out tests on the engine oriented on dynamic and emission characteristics using various portions of the before mentioned bio-components in diesel fuel are presented. Engine behaviour seemed to be improved in the presence of ethanol additives in D–RME blend with a reduction in pollutant emissions in exhaust gases, fuel consumption, ameliorated cetane number, ignition delay time and physical-chemical characteristics of the investigated compounds. The positive and negative aspects of applying bio-based additives in fossil diesel are reported and discussed.First published online: 24 Jun 2011